Alternative approach to autonomic instability of very severe tetanus: stellate ganglion block - Altıparmak,Başak (2018)
Abstract Tetanus is an acute and deadly disease caused by Clostridium tetani. A 60-year-old male came to hospital after he injured his thumb with a knife. Ten days later, he returned to hospital with abdominal spasms. He was vaccinated against tetanus and referred to intensive care unit. As he had sudden difficulty in respiration, he was entubated. Midazolam, magnesium and esmolol infusion were started. Next day, muscle spasms progressed all over his body. Midazolam infusion was replaced with propofol and vecuronium. At the third day, morphine infusion was added. At the 16th day, dexmedetomidine infusion was started. At the 20th day, ultrasound guided stellate ganglion block was performed to denervate sympathetic activity. The block was performed three times in a 10 days period. At the 30th, the patient recovered from very severe tetanus. The mainstay of tetanus treatment is adequate sedation. Neuroaxial blocks were proved to be effective for the control of sympathetic overactivity in recent years. Circulatory collapse remains to be the major cause of death. The mechanism is unclear but altered myocardial function is thought to be related to changeable catecholamine levels. The effect of stellate ganglion block on sympathetic and parasympathetic control of heart has been studied since the beginning of 1980s. Recently Scanlon et al. reported they treated a patient with medically refractory ventricular arrhythmias by ultrasound guided bilateral stellate ganglion block. In conclusion, stellate ganglion block can be an alternative method when the autonomic storm cannot be controlled with medical agents.